Cover Image. (3rd January 2019) - Li, Yingjie; Feng, Yaping; Cao, Pinyin; Ke, Jin; Fang, Wei; Cai, Hengxing; Deng, Mohong; Long, Xing
Abstract : The cover image is based on the Original Article Role of synovium‐derived fibrous cartilage in temporomandibular joint synovial chondromatosis, by Yingjie Li et al., DOI:10.1111/jop.12788 .